The Determinant of Hypertension on Pre-Elderly and Elderly Prolanis in Sukowono Primary Health Center Jember Regency in 2019 - Rahmad, Ardhi Nur; Ningtyias, Farida Wahyu; Rohmawati, Ninna (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Hypertension is a main health problem throughout the world, in addition to its high prevalence, hypertension is also associated with an increased risk of cardiovascular disease. The reasearch was to analyze the relation between levels of sosialeconomic, levels of sodium and saturated fat consumption, the levels of physical activity, nutritional status, coffee, smoking, and the levels of stress with hypertension of Prolanis pre-elderly and elderly in Sukowono Primary Health Center, Jember Regency. The research was observational analytic study with cross sectional design. The population of this research were 48 respondents. The sampling technique was total sampling. The data analyzed by using bivariate analysis with Chi-Square test. The result of analysis in this research showed that there was a correlation between the level of sodium consumption with the incidence of hypertension. There was no correlation between socioeconomic (employment and the minimum earning) (p-value = 0.282 and p-value = 0.770 > 0.05), the levels of saturated fat (p-value = 1.000 > 0.05), the levels of physical activity (p-value = 0.074 > 0.05), nutritional status (p-value = 0.799 > 0.05), consumption coffee (p-value = 1.000 > 0.05), smoking (p-value = 1.000 > 0.05), and the levels of stress (p-value = 0.126 > 0.05) with hypertension. There was correlation between the levels of sodium consumption with hypertension (p-value = 0.000 < 0.05).